2003
DOI: 10.1177/0310057x0303100532
|View full text |Cite
|
Sign up to set email alerts
|

Terlipressin Infusion in Catecholamine-resistant Shock

Abstract: Catecholamine-resistant shock is not uncommon in intensive care. Bolus dose terlipressin (a vasopressin analogue) has been used successfully in this setting allowing cessation of other vasopressor agents. The relative vasopressin deficiency in combination with the restoration of the vascular tone (by blocking adenosine triphosphate potassiumsensitive channels) by exogenous vasopressin may be the explanation of these beneficial effects. We describe a case report where the use of a continuous terlipressin infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…Plasma levels of lysine vasopressin increase 40 to 60 minutes after bolus injection of terlipressin, peaking at 60 to 120 minutes after administration (70-100 pmol/L) [ 11 , 12 ]. In recent years, several studies investigated the feasibility of continuous terlipressin infusion in both the experimental [13][14][15] and clinical settings [16][17][18]. Unfortunately, no pharmacokinetic data are available on the latter approach.…”
Section: Physiology and Pharmacology Of Arginine Vasopressin And Terlmentioning
confidence: 99%
“…Plasma levels of lysine vasopressin increase 40 to 60 minutes after bolus injection of terlipressin, peaking at 60 to 120 minutes after administration (70-100 pmol/L) [ 11 , 12 ]. In recent years, several studies investigated the feasibility of continuous terlipressin infusion in both the experimental [13][14][15] and clinical settings [16][17][18]. Unfortunately, no pharmacokinetic data are available on the latter approach.…”
Section: Physiology and Pharmacology Of Arginine Vasopressin And Terlmentioning
confidence: 99%
“…However, the patients treated with TP as first-line vasopressor survived and showed no signs of TP-related AEs. Taken together, with results from experimental studies (Asfar et al, 2005;Lange et al, 2007) and previous clinical case reports (Jolley et al, 2003;Zeballos et al, 2006), early low-dose infusion of TP may potentially be superior to a later resort strategy in septic shock. Recently, Xiao et al (2016) reported that low dose of TP continuous infusion combined with NE has synergistic effect in septic shock patients.…”
Section: The Significance Of This Study For Future Clinical Practice mentioning
confidence: 59%
“…Die verwendeten AVP-Dosierungen reichen von 0,0 U*min − bis zu ,8 U*min − [28,32]; bei Anwendung von TP wurden entweder repetitive Bolusinjektionen von weniger als  mg [4] bis zu 2 mg [43] oder eine kontinuierliche Infusion von 250-500 µg*h − appliziert [26] Da es bisher keine prospektiven, placebokontrollierten Studien, sondern nur Fallberichte zur TP-Anwendung bei Sepsis und SIRS gibt, sind wertende Aussagen über die Wirkungen von TP bei Hypotonie im Rahmen systemischer Entzün-dungsreaktionen schwierig. Bisherige Erfahrungen zeigen jedoch, dass auch TP die Vasodilatation antagonisieren und somit den MAD stabilisieren kann [26,40,43], so dass ein erleichtertes Ausschleichen konventioneller Vasopressoren mög-lich ist [43]. Die Blutdrucksteigerung geht allerdings sowohl in den klinischen Studien als auch in den tierexperimentellen Untersuchungen regelmäßig mit einer deutlichen Reduktion von HZV und HF einher [26,40,43,70].…”
Section: Bisherige Erfahrungen Bei Septischen Patientenunclassified
“…Bisherige Erfahrungen zeigen jedoch, dass auch TP die Vasodilatation antagonisieren und somit den MAD stabilisieren kann [26,40,43], so dass ein erleichtertes Ausschleichen konventioneller Vasopressoren mög-lich ist [43]. Die Blutdrucksteigerung geht allerdings sowohl in den klinischen Studien als auch in den tierexperimentellen Untersuchungen regelmäßig mit einer deutlichen Reduktion von HZV und HF einher [26,40,43,70].…”
Section: Bisherige Erfahrungen Bei Septischen Patientenunclassified